Nodular Worm Infections in Wild Non-human Primates and Humans Living in the Sebitoli Area (Kibale National Park, Uganda): Do High Spatial Proximity Favor Zoonotic Transmission? - Marie Cibot; Jacques Guillot; Sophie Lafosse; Céline Bon; Andrew Seguya; Sabrina Krief (Public Library of Science (PLoS), 2015)
BACKGROUND:Nodular Oesophagostomum genus nematodes are a major public health concern in some African regions because they can be lethal to humans. Their relatively high prevalence in people has been described in Uganda recently. While non-human primates also harbor Oesophagostomum spp., the epidemiology of this oesophagostomosis and the role of these animals as reservoirs of the infection in Eastern Africa are not yet well documented. METHODOLOGY/PRINCIPAL FINDINGS:The present study aimed to investigate Oesophagostomum infection in terms of parasite species diversity, prevalence and load in three non-human primates (Pan troglodytes, Papio anubis, Colobus guereza) and humans living in close proximity in a forested area of Sebitoli, Kibale National Park (KNP), Uganda. The molecular phylogenetic analyses provided the first evidence that humans living in the Sebitoli area harbored O. stephanostomum, a common species in free-ranging chimpanzees. Chimpanzees were also infected by O. bifurcum, a common species described in human populations throughout Africa. The recently described Oesophagostomum sp. found in colobine monkeys and humans and which was absent from baboons in the neighboring site of Kanyawara in KNP (10 km from Sebitoli), was only found in baboons. Microscopic analyses revealed that the infection prevalence and parasite load in chimpanzees were significantly lower in Kanyawara than in Sebitoli, an area more impacted by human activities at its borders. CONCLUSIONS/SIGNIFICANCE:Three different Oesophagostomum species circulate in humans and non-human primates in the Sebitoli area and our results confirm the presence of a new genotype of Oesophagostomum recently described in Uganda. The high spatiotemporal overlap between humans and chimpanzees in the studied area coupled with the high infection prevalence among chimpanzees represent factors that could increase the risk of transmission for O. stephanostomum between the two primate species. Finally, the importance of local-scale research for zoonosis risk management is important because environmental disturbance and species contact can differ, leading to different parasitological profiles between sites that are close together within the same forest patches.